Caddeddi on the Tellaro - Wilson, Roger John Anthony, 1949- (Leuven)
viii, 200 s.
Keywords: "The late Roman villa of Caddeddi, near Noto in south-east Sicily, first came to light over forty years ago. Built in the second half of the fourth century AD, it is chiefly known for its three figured mosaic pavements, which after careful restoration in Syracuse were returned to the site prior to its opening to the public in 2008. This book describes in details these an other pavements at Caddeddi, and concludes that, as at the more famous villa of Casale near Piazza Armerina a generation before, they are like to be the work of North African mosaicists fulfilling an overseas commission for the villa's owner." --